Quality of Sexed Sperm of Bali Bull in Regional Artificial Insemination Center of Riau Province - Yendraliza Yendraliza; Anwar Efendi Harap; July Handoko; Muhammad Rodiallah (Buletin Peternakan, 2019)
This study aimed to evaluate the quality of frozen semen of Bali bull resulted from sexing procedure on calf or offspring production with desired sex. The tested sperm of Bali bull were collected from Bali bull raised at Regional Artificial Insemination Center of Riau Province (BIBD Riau). The study was carried out in 2 stages. The first stage was X and Y chromosome separation by albumin method. The extender used in the sexing procedure is trice citrate fructose and egg yolk. The second stage was mainly testing the sexed sperm collected in 60 Bali cow in Langkat Village, Bengkalis Regency. To determine the quality of post thawing frozen semen collected from the sexing procedure, the study evaluated motility, viability, mortality, abnormality and plasma membrane integrity of the spermatozoa. The pregnancy rate, calving rate, and birth accuracy of inseminated sexed sperm to offspring’ sex were also evaluated. The evaluation resulted in motility (66.3-75.3%), viability (70-78.5%), plasma membrane integrity (60-65.8%), abnormality (6.05-8.05%), mortality (20.05-30.05%), and pregnancy rate (83.33-90%). The calving rate on this study was 100% with the birth accuracy of 81.8% for male offspring and 40% for female offspring. As conclusion, the sexed sperm evaluated on this study have fairly good fertility.